A new species of Tapajosa Melichar from Curaçao, Lesser Antilles (Hemiptera: Cicadellidae: Proconiini) - Haas, Matthé Cornelis De; Gaiani, Marco A. (Zootaxa, 2024)
A new species of the Neotropical genus Tapajosa Melichar 1924 from Curaçao is proposed, described, and illustrated. Tapajosa arawaka sp. nov. differs from other species of the genus mainly in the shape of male genitalia. Its close morphological affinity with Tapajosa spinata Young, 1968 suggests that ancestors of the new species migrated from mainland Venezuela.